CHALLENGES OF STATE OF EXCEPTION IN CONSTITUTIONAL PROCESS - Heiss, Claudia (Política. Revista de Ciencia Política, 2020)
This article analyzes the states of exception from the review of their main elements from the perspective of democratic theory and its application in the constitutional and political history of Chile since the 19th century. He argues that the evolution of the states of exception in the Chilean constitutions of 1833, 1925 and 1980 evidences a pattern of institutional dependence, where the previous frameworks significantly determine the later design and that the institutional design has not been focused on the protection of the citizens. The state of siege has given power without due responsibility, and has been used frequently for political and social repression, and not for the preservation of the community.